Supplementary file 1_Climate change may improve physiological suitability for three widespread Mexican snakes.docx - Ricardo Figueroa-Huitrón (21453962) (2025)
Introduction Thermal tolerance and performance breadth can define the suitable areas where reptiles can survive and perform at an optimal physiological level. It is important to determine the distribution of suitable areas for reptile physiology and to assess how they could change in future climate change scenarios. In this paper, we utilized a mechanistic approach to model current and future physiological suitability of three snakes endemic to Mexico: Crotalus polystictus, Conopsis lineata and Thamnophis melanogaster. Methods Utilizing thermal physiology data previously generated, we modeled operative temperatures in the present and in 2070, under SSP3-7.0 and SSP5-8.5. We utilized performance breadth as the suitability threshold and calculated the amount of daily and annual hours that fall within this range in each grid cell of the accessibility areas of the three species Results We found that suitability is at its highest on the pine-oak forests in mountainous regions. Future scenarios will provide wider windows with favorable temperatures, and the suitability of the three species will increase in most of their accessible areas. On average, annual hours of physiological suitability will increase by 103% and 133% (under SSP3-7.0 and SSP5-8.5, respectively) for C. polystictus, 12% and 14% for C. lineata, and 17% and 20% for T. melanogaster Discussion These results show that the thermal environments of the mountainous regions of Mexico are very important for the sustenance of these species in a changing world. These areas are hotspots for reptile biodiversity, but they face problems of area reduction. Further research considering the effect of temperature on reproduction or the change in precipitation, would provide a broader picture about the physiological responses of these species. Integrating physiological information like this in a geographical context is important to designing adequate conservation strategies for reptiles.